2013
DOI: 10.1053/j.gastro.2013.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Mas Receptor by Angiotensin-(1–7) in the Renin–Angiotensin System Mediates Mesenteric Vasodilatation in Cirrhosis

Abstract: In the splanchnic vessels of patients and rats with cirrhosis, increased levels of ACE2 appear to increase production of Ang-(1-7), which leads to activation of MasR and splanchnic vasodilatation in rats. This mechanism could cause vascular hypocontractility in patients with cirrhosis, and might be a therapeutic target for portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
125
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 50 publications
12
125
1
3
Order By: Relevance
“…Another study in splanchnic vessels of patients and rats with cirrhosis suggested a role for the ACE2/Ang(1-7)/Mas axis to explain the vascular hypocontractility (35). In our study, Ace2 and Mrga (Mas receptor) gene expression were upregulated in EVAT of Adipo-MROE mice, supporting other studies that have demonstrated hypocontractility (35).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another study in splanchnic vessels of patients and rats with cirrhosis suggested a role for the ACE2/Ang(1-7)/Mas axis to explain the vascular hypocontractility (35). In our study, Ace2 and Mrga (Mas receptor) gene expression were upregulated in EVAT of Adipo-MROE mice, supporting other studies that have demonstrated hypocontractility (35).…”
Section: Discussionsupporting
confidence: 89%
“…In Ccl4-induced cirrhotic rats, H 2 O 2 has been directly implicated in regulating mesenteric hypocontractility to noradrenaline through the Rho kinase signaling pathway (34). Another study in splanchnic vessels of patients and rats with cirrhosis suggested a role for the ACE2/Ang(1-7)/Mas axis to explain the vascular hypocontractility (35). In our study, Ace2 and Mrga (Mas receptor) gene expression were upregulated in EVAT of Adipo-MROE mice, supporting other studies that have demonstrated hypocontractility (35).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms have been shown to be involved in activation of the eNOS signaling pathway under this pathological condition, including upregulation of GTP cyclohydrolase I, mediated by bacterial translocation, with production of tetrahydrobiopterin (cofactor of eNOS) [18], phosphorylation of eNOS by Akt [19], and coupling of eNOS with chaperone heat shock protein 90 [20]. Recently, a new mechanism for eNOS modulation in cirrhosis, involving the renin-angiotensin system, was shown [21]. Angiotensin-converting enzyme (ACE) 2 cleaves angiotensin II to generate the vasodilator angiotensin-(1-7), which binds to the receptor Mas (MasR), leading to the activation of eNOS and the endothelial production of NO.…”
Section: Increased Circulating Vasodilatorsmentioning
confidence: 99%
“…Hemodynamic studies were performed under ketamine/xylazine anesthesia (78mg/kg / 12.5mg/kg i.p.) as previously described [14][15][16][17]. Rats were fasted overnight but allowed free access to water.…”
Section: Animalsmentioning
confidence: 99%
“…Hemodynamics were investigated using the coloured microsphere technique as previously described [14][15][16][17]. The colored microsphere technique was validated by the more frequently used radioactive microsphere method [18].…”
Section: Animalsmentioning
confidence: 99%